Penyetiran Opini Publik di Media Massa: Telaah Teori Konspirasi atas Pelemahan Islam - Wanodya, Ayusta Gilang (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
Public opinion is recognized as a panacea in various sectors of life whether political, economic, or religious. Those who want power rally to drive public opinion. There are various conspiracy theories in the minds of people. This study aims to examine the phenomenon in the Indonesian society who suspect that there is a conspiracy to steer public opinion by the mass media to weaken Muslims. The research method used is library research. The study found that the reasons people believe in conspiracy theories are as follows; (1) Western-phobia, like the west with its Islam-phobia, Muslims also have Western-phobia, (2) Hyper-logical to the linear relationship between purpose, action and effect, no place for unplanned consequences, (3) The antidote bidder, the public wants to know what is going on, as a result they choose to fill the plot holes with their fantasies. The expected implication of this research is that we do not trust one hundred percent of conspiracy theories in circulation, and even if the conspiracy is true, blaming the other is not a wise and effective solution to solving the problems of contemporary Muslims.